Aquisição da concordância nominal de número: um estudo de caso (Revista de Estudos da Linguagem, 2006)
This paper aims at investigating the acquisition of number agreementwithin DP by a child acquiring Brazilian Portuguese, under theassumptions of the Minimalist Program (Chomsky, 1998; 1999). Inthe analysis of the child’s speech production, I highlight the mostfrequent patterns of number agreement and plural marking, and discussthree hypotheses (Carstens, 2000; Lopes, 2004; Magalhães, 2004) tofind the one which explains the variation within the child’s own speechand also between child and adult registers; such hypothesis should alsobe able to predict how the infant’s number agreement patterns willevolve into the adult system. The proposal by Carstens (2000) is theonly one which supports the patterns found in the data under analysis,especially the variation between the adult patterns of agreement andplural marking vs. the occurrence, in child language, of plural markingmorpheme (-s) only on nouns, which is ungrammatical in adult registers.